دور اللوحات الرقمية في زيادة التحصيل الدراسي لمتعلمي المرحلة الابتدائية - المقدم,تفاحة; زوزو,فتيحة (University of Eloued جامعة الوادي, 2024)
ترجع أهمية هذه الدراسة بعدما أصبحت اللوحات الرقمية جزءا كبيرا ومهما في مجال التعليم وذلك عن طريق إستخدامها كوسيلة للتعلم داخل القسم. حيث إعتمدت الدراسة على المنهج الوصفي،كما وتمثلت أداة جمع البيانات في الإستبيان الذي وزع على مجتمع الدراسة، والذي تكون من 60 أستاذ وأستاذة من أساتذة مدارس التعليم الإبتدائي لولاية تقرت.التي تستخدم اللوحات الرقمية في عملية التعليم . أما المقاربات النظرية للدراسة فتمثلت في نظرية الإستخدامات والإشباعات ونظرية الحتمية التكنولوجية، وقد توصلت الدراسة لجملة من النتائج كان منها : 1ـ سهولة إستخدام اللوحات الرقمية بالنسبة للمتعلمين من المرحلة الإبتدائية . 2 ـ زيادة إنتباها لمتعلمين في الحصة التي يتم فيها إستخدام اللوحات الرقمية . 3- خففت اللوحات الرقمية عبء حمل الكتب الورقية بالنسبة للمتعلمين . The importance of this study emerged as digital boards have become a significant and essential part of education, serving as a means of instruction. The current study aims to determine the role of digital boards in enhancing academic achievement among elementary learners from the perspective of primary education teachers. The study employed a descriptive approach and utilized a questionnaire as a data collection tool distributed among a sample of 60 teachers from primary schools in Touggourt province. The study relied on two theories, namely, the Uses and Gratifications Theory and the Technological Determinism Theory. To discuss the study's hypotheses, several findings were reached, including: 1/Ease of use of digital boards for learners. 2/ Increased attention of learners during the session due to the use of digital boards. 3/Digital boards alleviated the burden of carrying physical books for learners.
من وجهة نظر أساتدة التعليم الابتدائي
Keywords: لوحات الرقمية; التحصيل الدراسي; Digital boards; academic achievement